Novel quaternary ammonium salt grinding aid and application thereof in cement

Through the development of new type of monuer ammonium salt abrasives, its unique molecular structure and polarity are adsorbed on the surface of the cement particles, which solves the problem of complex, high cost and insufficient mechanical performance of the existing cement abrasives, and achieved significant improvement of cement. The effect of helping the grinding effect and mechanical properties.

CN119371325AActive Publication Date: 2025-01-28HUIZHOU SUNWORK NEW TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411488794.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing cement grinding aids have complex processes, high costs and need to be improved in mechanical properties, making it difficult to effectively improve the grinding effect and mechanical properties of cement.

Method used

The development of a new type of daily ammonium salt abrasive, which is prepared through a daily ammonium response, introduced multiple hydroxyl groups and ductinium salts. It has a unique molecular structure and polarity. Fineness and mechanical properties.

Benefits of technology

The new type of monopoly ammonium salt aid has significantly improved the grinding effect and mechanical performance of the cement. It is far better than the existing trimethalamine aids, which can better disperse cement particles, improve fineness, promote hydration, enhance hydrophilization The denseness of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099423540000021
    Figure BDA0005099423540000021
  • Figure BDA0005099423540000022
    Figure BDA0005099423540000022
  • Figure BDA0005099423540000023
    Figure BDA0005099423540000023
Patent Text Reader

Abstract

The invention belongs to the technical field of cement production, and particularly relates to a novel quaternary ammonium salt grinding aid and application thereof in cement. The prepared novel quaternary ammonium salt grinding aid can improve the grinding aid effect of cement and improve the mechanical property of the cement. On one hand, a plurality of hydroxyls and quaternary ammonium salt are introduced into the grinding aid prepared by the preparation method, and the grinding aid can be well adsorbed on the surfaces of cement particles and shield charges due to the unique molecular structure and polarity of the grinding aid, so that a good grinding aid effect is achieved, a good dispersion effect is achieved, and the fineness of cement is improved; on the other hand, the grinding aid can better promote the hydration speed of cement clinker, more hydration products are generated, the cement hydration products are denser in body structure, and therefore the mechanical property of cement is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement production, and in particular relates to a novel quaternary ammonium salt grinding aid and application thereof in cement. Background Art

[0002] my country is a large cement producer. Cement plays a very important role in the development of the national economy. It is widely used in national defense projects, bridge and road projects, civil housing, commercial and residential construction projects, etc. The main process of cement production includes three processes: grinding of raw materials, burning of clinker and grinding of cement clinker. In this process, the energy consumption of grinding is the highest, and the energy loss rate in the grinding process is very high, and the utilization rate is quite low. The energy consumed in the clinker grinding process accounts for at least half of the total energy. Only a small part of the energy is used to increase the material grinding, and most of the other energy is wasted. The reason is that the fineness of the material continues to increase during the grinding process. If the cement reaches a sufficient fineness but cannot be discharged from the mill in time, this will produce a cushion layer to a certain extent, so that the material in the mill will impact, collide and grind again, consuming more energy; in addition, the adhesion and interfacial tension of the powder will also increase with the increase of fineness, which will cause the cracks formed in the particles to heal again, increasing the energy consumption of re-grinding. In short, all of the above will have a serious impact on the grinding efficiency of the grinding equipment and greatly reduce the utilization rate of energy. In cement production, since energy consumption and grinding efficiency are the main factors restricting its development, improving its grinding efficiency and reducing energy consumption have become the top priority that the cement industry urgently needs to solve.

[0003] In order to improve grinding efficiency, reduce energy consumption and save energy, domestic cement companies currently generally adopt two measures. One is to improve the grinding method and grinding process by improving the mechanical structure of the grinding system to achieve energy saving; the other measure is to add a small amount of grinding aids to the grinding material to achieve the purpose. The first measure can improve grinding efficiency and reduce energy consumption to a certain extent, but it generally requires the addition of mechanical equipment, which greatly increases the investment cost of cement production; while the second measure is simple to operate, requires less investment, and is quick to take effect, and can well improve cement performance.

[0004] CN116396447B discloses a preparation method and application of a polymer cement grinding aid, however, the polymer cement grinding aid has a complex process, high cost, and its mechanical properties need to be improved.

[0005] CN108467456B discloses a polycarboxylic acid polyhydroxy ester type cement grinding aid and a preparation method thereof. However, the grinding aid is also a polymer material with high cost and is not suitable for industrial production.

[0006] Based on this, there is an urgent need to develop a new grinding aid that can improve the grinding effect of cement and improve the mechanical properties of cement. Summary of the invention

[0007] In view of the problems existing in the prior art, the object of the present invention is to provide a new type of quaternary ammonium salt grinding aid that can improve the grinding effect of cement and improve the mechanical properties of cement. The present invention is achieved by the following technical solutions:

[0008] A novel quaternary ammonium salt grinding aid, which is a compound shown in formula (I):

[0009]

[0010] Where R is C 1-6 Alkyl or C 3-8 Cycloalkyl, X is Cl, Br, I, BF4 or CF3SO3.

[0011] In some embodiments, R is methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, cyclopropyl, cyclobutyl, or cyclopentyl.

[0012] In some embodiments, X is Cl, Br, I.

[0013] In some embodiments, it is a compound having one of the following structures:

[0014]

[0015] In some embodiments, the preparation method of the novel quaternary ammonium salt grinding aid comprises the following steps:

[0016] Compound (II) and compound (III) are subjected to quaternization reaction to obtain a compound represented by formula (I), and the reaction formula is as follows:

[0017]

[0018] In some embodiments, the reaction solvent is selected from one or more of water, methanol, ethanol, and isopropanol.

[0019] In some embodiments, the molar ratio of compound (II) to compound (III) is (2.0-2.5):1; the reaction temperature is 50-80°C, and the reaction time is 5-10h.

[0020] The present invention also protects a cement composition comprising the novel quaternary ammonium salt grinding aid.

[0021] In some embodiments, the cement composition comprises clinker, gypsum, limestone, fly ash, slag and a novel quaternary ammonium salt grinding aid.

[0022] The present invention also protects the application of the novel quaternary ammonium salt grinding aid in cement.

[0023] The present invention has achieved the following beneficial effects:

[0024] 1) The novel quaternary ammonium salt grinding aid prepared by the present invention can improve the grinding effect of cement and improve the mechanical properties of cement, and its effect is far superior to the common triethanolamine grinding aid in the prior art.

[0025] 2) The grinding aid prepared by the present invention introduces multiple hydroxyl groups and quaternary ammonium salts, and its unique molecular structure and polarity enable it to be well adsorbed on the surface of cement particles, shielding charges, and playing a good grinding aid effect, thereby playing a good dispersing effect and improving the fineness of cement; on the other hand, the grinding aid of the present invention can better promote the hydration rate of cement clinker, produce more hydration products, make the body structure of cement hydration products more compact, thereby improving the mechanical properties of cement. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The endpoints and any values ​​of the scope described in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.

[0028] Preparation Example 1: Preparation of Novel Quaternary Ammonium Salt Grinding Aid A

[0029]

[0030] Anhydrous ethanol (300 mL) was added to a three-necked flask equipped with a stirrer and a reflux condenser, followed by the raw material compound 1 (50.0 g, 0.22 mol) and 1,3-dibromopropane (20.0 g, 0.1 mol), and the temperature was raised to 75°C for reflux stirring and reaction for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and vacuum distilled and concentrated to obtain a light yellow viscous substance, which was then washed three times with a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:2, and a white solid was obtained by suction filtration. The new quaternary ammonium salt grinding aid A was obtained by vacuum drying at 100°C, and the yield was 71.5%.

[0031] 1H NMR (400MHz, DMSO-d6): δ5.45(s,4H),3.55-3.50(m,4H),2.61-2.54(m,4H),2.40-2 .36(m,4H),2.25(s,6H),1.57-1.46(m,16H),1.40-1.35(m,2H),1.23-1.11(m,16H).

[0032] In addition, new quaternary ammonium salt grinding aids B, C and D can be prepared by a similar method.

[0033] 1) Preparation of new quaternary ammonium salt grinding aid B

[0034]

[0035] Anhydrous ethanol (300 mL) was added to a three-necked flask equipped with a stirrer and a reflux condenser, followed by the raw material compound 1 (50.0 g, 0.22 mol) and 1,3-dichloropropane (11.3 g, 0.1 mol), and the temperature was raised to 70°C for reflux stirring and reaction for 7 hours. After the reaction was completed, the mixture was cooled to room temperature, and vacuum distilled and concentrated to obtain a light yellow viscous substance, which was then washed three times with a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:2, and a white solid was obtained by suction filtration. The new quaternary ammonium salt grinding aid B was obtained by vacuum drying at 100°C, with a yield of 64.2%.

[0036] 2) Preparation of new quaternary ammonium salt grinding aid C

[0037]

[0038] Anhydrous ethanol (300 mL) was added to a three-necked flask equipped with a stirrer and a reflux condenser, followed by the raw material compound 2 (53.0 g, 0.22 mol) and 1,3-dibromopropane (20.0 g, 0.1 mol), and the temperature was raised to 75°C for reflux stirring and reaction for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and vacuum distilled and concentrated to obtain a light yellow viscous substance, which was then washed three times with a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:2, and a white solid was obtained by suction filtration. The new quaternary ammonium salt grinding aid C was obtained by vacuum drying at 100°C, with a yield of 67.9%.

[0039] 3) Preparation of new quaternary ammonium salt grinding aid D

[0040]

[0041] Anhydrous ethanol (300 mL) was added to a three-necked flask equipped with a stirrer and a reflux condenser, followed by the raw material compound 2 (53.0 g, 0.22 mol) and 1,3-dichloropropane (11.3 g, 0.1 mol), and the temperature was raised to 70°C for reflux stirring and reaction for 7 h. After the reaction was completed, the mixture was cooled to room temperature, and vacuum distilled and concentrated to obtain a light yellow viscous substance, which was then washed three times with a mixed solvent of ethyl acetate and acetone in a volume ratio of 1:2, and a white solid was obtained by suction filtration. The new quaternary ammonium salt grinding aid D was obtained by vacuum drying at 100°C, with a yield of 62.7%.

[0042] Application Examples

[0043] Take new quaternary ammonium grinding aid A, new quaternary ammonium grinding aid D, and common quaternary ammonium grinding aid triethanolamine, refer to the following cement mix ratio to prepare samples, and test the relevant properties:

[0044] The cement ratio (mass fraction) is: clinker 70%, gypsum 5%, limestone 6%, fly ash 9%, slag 10%. Grinding conditions: ф500mm x 500mm ball mill, grinding aid dosage is 0.05% (compared to the total weight of cement), grinding for 40 minutes.

[0045] The performance test method is as follows:

[0046] 1) Determine the cement fineness according to the water sieving method in GB1345-2005 "Test Method for Cement Fineness" (80μm Sieve Sieve Analysis Method). The experimental steps are as follows: Before the sieving test, check that there is no mud or sand in the water, adjust the water pressure and the position of the water sieve frame so that it can operate normally, and control the distance between the bottom of the nozzle and the sieve to be 35mm~75mm. Weigh the sample accurately to 0.01g, place it in a clean water sieve, immediately rinse it with fresh water until most of the fine powder passes through, place it on the water sieve frame, and rinse it continuously for 3 minutes with a nozzle with a water pressure of 0.05MPa±0.02MPa. After sieving, use a small amount of water to flush the sieve residue into the evaporating dish. After all the cement particles have settled, carefully pour out the clean water, dry it, and weigh all the sieve residue with a balance.

[0047] 2) The flexural strength of cement mortar was determined according to GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The experimental steps are as follows: the mortar that meets the consistency requirements is made into a 40mmx40mmx160mm prism specimen, placed in a standard curing box with a constant temperature of 25°C and a relative humidity of 95%, and cured for 3d and 28d respectively, and then measured.

[0048] 3) According to GB / T17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", the compressive strength of cement mortar is determined. The experimental steps are as follows: a 40mm x 40mm x 160mm prism specimen model is used to make a module of mortar that meets the consistency requirements, and it is placed in a standard curing box with a constant temperature of 25°C and a relative humidity of 95%. It is cured for 3d and 28d respectively, and the compressive strength of cement mortar is measured. During the test, the difference between the center of the half prism and the pressure center of the press plate should be within ±0.5mm, and the part of the prism exposed outside the press plate is about 10mm. During the entire loading process, the load is evenly applied at a rate of 2400±200N / s until it is destroyed.

[0049] The test results are shown in Table 1:

[0050] Table 1 Cement performance test results

[0051]

[0052]

[0053] As shown in Table 1, the novel quaternary ammonium salt grinding aid prepared by the present invention can improve the grinding aid effect of cement and improve the mechanical properties of cement, and its effect is far superior to the common triethanolamine grinding aid of the prior art. The main reason is that: on the one hand, the grinding aid prepared by the present invention introduces multiple hydroxyls and quaternary ammonium salts, and its unique molecular structure and polarity enable it to be well adsorbed on the surface of cement particles, shielding electric charge, playing a good grinding aid effect, thereby playing a good dispersing effect, and improving the fineness of cement; on the other hand, the grinding aid of the present invention can better promote the hydration speed of cement clinker, produce more hydration products, make the cement hydration product body structure more dense, thereby improving the mechanical properties of cement.

[0054] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A novel quaternary ammonium salt grinding aid, which is a compound shown in formula (I): in, R is C 1-6 Alkyl or C 3-8 Cycloalkyl, X is Cl, Br, I, BF4 or CF3SO3.

2. The novel quaternary ammonium salt according to claim 1, characterized in that R is methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, cyclopropyl, cyclobutyl or cyclopentyl.

3. The novel quaternary ammonium salt according to claim 1, characterized in that X is Cl, Br, or I.

4. The novel quaternary ammonium salt according to claim 1, which is a compound having one of the following structures:

5. A method for preparing the novel quaternary ammonium salt grinding aid according to claim 1, comprising the following steps: Compound (II) and compound (III) are subjected to quaternization reaction to obtain a compound represented by formula (I), and the reaction formula is as follows: Wherein, R and X are defined as in claim 1.

6. The method according to claim 5, characterized in that The reaction solvent is selected from one or more of water, methanol, ethanol and isopropanol.

7. The method according to claim 5, characterized in that The molar ratio of the compound (II) to the compound (III) is (2.0-2.5):1; the reaction temperature is 50-80°C, and the reaction time is 5-10h.

8. A cement composition, characterized in that The novel quaternary ammonium salt grinding aid comprises the novel quaternary ammonium salt grinding aid according to any one of claims 1 to 4.

9. The cement composition according to claim 8, characterized in that Contains clinker, gypsum, limestone, fly ash, slag and new quaternary ammonium salt grinding aid.

10. Use of the novel quaternary ammonium salt grinding aid according to any one of claims 1 to 4 in cement.

Citation Information

Patent Citations

  • A polycarboxylate polyhydroxy ester type cement grinding aid and its preparation method

    CN108467456B

  • Cement grinding aid

    CN105271880A

  • Lignocellulose type cement grinding aid and preparation method thereof

    CN109320129A